2006
DOI: 10.1111/j.1472-8206.2006.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of exogenous cAMP to improve vascular endothelial dysfunction in hypertensive rats

Abstract: The study has been designed to investigate the effect of 8-Br-cAMP, an activator of protein kinase A, in hypertension-induced vascular endothelial dysfunction. Rats were uninephroctomized and desoxycortisone acetate (DOCA) (40 mg/kg, s.c.) was administered to rats to produce hypertension (mean arterial blood pressure > 140 mmHg). Vascular endothelial dysfunction was assessed using isolated aortic ring preparation, electron microscopy of thoracic aorta and serum concentration of nitrite/nitrate. The expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…In the present study, Br-cAMP or Db-cAMP pretreatment to cells led to significant reversal of CRP-mediated inhibition of GTPCH1 activity (Fig 3c). Furthermore, eNOS dysfunction has been reported to be attenuated via cAMP/PKA pathway activation [31,32]. The pretreatment of HAECs with cAMP analogues led to significant reversal of CRP-mediated eNOS inhibition (Fig 3d and e) in the present study.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In the present study, Br-cAMP or Db-cAMP pretreatment to cells led to significant reversal of CRP-mediated inhibition of GTPCH1 activity (Fig 3c). Furthermore, eNOS dysfunction has been reported to be attenuated via cAMP/PKA pathway activation [31,32]. The pretreatment of HAECs with cAMP analogues led to significant reversal of CRP-mediated eNOS inhibition (Fig 3d and e) in the present study.…”
Section: Resultssupporting
confidence: 58%
“…In this context, cell permeable analogue of cAMP, 8 Br-cAMP, which activates protein kinase A has been shown not only to result in restoration of GTPCH1 activity [26], but also attenuation of eNOS dysfunction [31,32]. Importantly, Hashimoto et al [43] reported the activation of eNOS by cilostazol via a cAMP/PKA and PI3K/Akt dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in streptozotocin-induced diabetic rats could show a decreased renal eNOS protein production 4 weeks after diabetes induction [15]. In addition, reduced eNOS mRNA was found to be present in aortic and myocardial tissues from diabetic rats [13]. There is growing evidence for an emerging role of NO derived from eNOS in vascular defence against cardiovascular diseases [5].…”
Section: Discussionmentioning
confidence: 98%
“…While low eNOS levels have been found in diabetic aortic, renal and heart tissues [13][14][15], it remains yet unknown whether or not the NO-cGMP signalling axis can be reconstituted by an enhancement of eNOS production under these conditions. In the present study we investigated the hypothesis that pharmacological enhancement of eNOS production with AVE3085, a novel eNOS enhancer, is sufficient to activate the NO-cGMP axis, attenuate inflammatory response, and improve peripheral endothelial function in a rat model of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…158) Our laboratory has reported that 8-Br-cAMP, an activator of PKA markedly prevented the dysfunction of vascular endothelium. 159,160) …”
Section: Future Directionsmentioning
confidence: 99%